Radix paeoniae alba polysaccharide attenuates lipopolysaccharide-induced intestinal injury by regulating gut microbiota - Li, Aoyun; Ding, Jinxue; Shen, Ting; Liang, Ying; Wei, Fan; Wu, Yi; Iqbal, Mudassar; Kulyar, Muhammad Fakhar-e-Alam; Li, Kun; Wei, Kunhua (Frontiers in Microbiology, 2023)
Accumulating evidence indicated that oxidative stress is closely related to inflammation and the progression of multiple chronic diseases, which seriously threaten the host health. Currently, multiple plant-derived polysaccharides have been demonstrated to ameliorate the negative effects of oxidative stress on the host, but the potential protective effect of radix paeoniae alba polysaccharide (RPAP) on host have not been well characterized. Here, we investigated whether different doses of RPAP administration could alleviate LPS-induced intestinal injury and gut microbial dysbiosis in mice. Results indicated that RPAP administration effectively alleviate LPS-induced intestinal damage in dose dependent. Additionally, amplicon sequencing showed that RPAP administration reversed the significant decrease in gut microbial diversity caused by LPS exposure and restored the alpha-diversity indices to normal levels. Microbial taxonomic investigation also indicated that LPS exposure resulted in significant changes in the gut microbial composition, characterized by a decrease in the abundances of beneficial bacteria (Lactobacillus, Alistipes, Bacillus, Rikenellaceae_RC9_gut_group, etc.) and an increase in the contents of pathogenic bacteria (Klebsiella, Helicobacter, Enterococcus, etc.). However, RPAP administration, especially in high doses, could improve the composition of the gut microbiota by altering the abundance of some bacteria. Taken together, this study demonstrated that RPAP administration could ameliorate LPS-induced intestinal injury by regulating gut microbiota. Meanwhile, this also provides the basis for the popularization and application of RPAP and alleviating oxidative stress from the perspective of gut microbiota.